Is the European short selling regulation a justifiable response to the concerns posed by short selling? - Howell, E (2015)
Short selling came onto the centre stage during the recent financial crisis when the collapse in price of financial listed securities after the demise of Lehman Brothers led to the introduction of a number of temporary short selling bans. In Europe however it was the commencement of the recent European sovereign debt crisis that was the true stimulus for proposing new short selling rules, the culmination of which was the introduction of the European Short Selling Regulation (the 'Regulation'). The thesis asks whether the Regulation is a justifiable response to the concerns posed by short selling. Such issues are measured against the relevant economic literature that almost overwhelmingly demonstrates that short selling contributes to market efficiency, that restrictions generally make markets less efficient and that constraints do not achieve the desired objective of stabilising prices. The thesis then analyses the political economy and backdrop to the Regulation’s introduction that largely dictated the shape of the final rules. The precise legislative choices made by Europe, including with respect to sovereign credit default swaps, are analysed, and (where relevant) there is a comparative element with a consideration of the US short sale regulations. These rules are used as a contrast and as a means of commenting more effectively on the European provisions. The doctorate concludes that the Regulation is not a justifiable response to policymakers' concerns and that the rules have suffered from the politicisation of the legislative process. The thesis suggests that short-term political point scoring has triumphed over the long-term benefits of market efficiency and that short sellers are now the subjects of highly technical rules that will negatively impair on market efficiency. Although, with time, parties may learn to use the new rules to their advantage, this does not justify the introduction of unreasonable rules in the first place.